Predicting the 28-Day Mortality of Non-Trauma Patients using REMS and RAPS; a Prognostic Accuracy Study - Garkaz, Omid; Rezazadeh, Farzin; Golfiroozi, Saeed; Paryab, Sahar; Nasiri, Sadaf; Mehryar , Hamidreza; Ghelichi-Ghojogh, Mousa (Archives of Academic Emergency Medicine, 2022)
Introduction: Various scoring systems have been designed for calculating the mortality risk of patients. This study evaluated the accuracy of Rapid Emergency Medicine Score (REMS) and Rapid Acute Physiology Score (RAPS) in predicting the 28-day mortality of non-trauma patients. Methods: This prospective cross-sectional study was conducted on 1003 adult non-trauma patients, who referred to the emergency department of Imam Khomeini Hospital, Urmia, Iran, in the second half of 2018, using the census sampling. We determined the screening performance characteristics of REMS and RAPS in predicting the 28-day mortality of patients. Results: This study examined 1003 non-trauma patients with a mean age of 61.5±18.05 years (60.6% male). The mean REMS (8.7 ± 3.2 vs. 6.0 ± 3.6; p < 0.001) and RAPS (3.7 ± 2.8 vs. 2.7 ± 2.0; p < 0.001) scores were significantly higher in deceased cases. Sensitivity and specificity of REMS in predicting the risk of non-trauma patients’ mortality were 85.19% (95%CI: 78.05% - 90.71%) and 78.34% (95%CI: 75.45% - 81.04%), respectively. While, the Sensitivity and specificity of RAPS in this regard were 61.39% (95%CI: 53.33% - 69.02%) and 71.12% (95%CI: 67.94% - 74.16%), respectively. The area under the receiver operating characteristic (ROC) curve of REMS and RAPS were 0.72 (95% CI: 0.68 -0.75) and 0.62 (95% CI: 0.56 - 0.65) in predicting the patients’ 28-day mortality, respectively (p = 0.001). Conclusion: The total accuracies of REMS and RAPS in predicting the 28-day mortality of non-trauma patients were in good and poor range, respectively. The screening performance characteristics of REMS were a little better in this regard.